2006
DOI: 10.1038/sj.leu.2404201
|View full text |Cite
|
Sign up to set email alerts
|

HCV-NS3 and IgG-Fc crossreactive IgM in patients with type II mixed cryoglobulinemia and B-cell clonal proliferations

Abstract: We demonstrate that in three cases of MC (two with immunocytoma), the IgM-RF þ component of their cryoprecipitated represents the circulating counterpart of the B-cell receptor (BCR) of the monoclonal overexpanded B-cell population. These IgMs were isolated and used to demonstrate a crossreactivity against both hepatitis C virus (HCV) NS3 antigen and the Fc portion of IgG. Epitopes were identified in a fraction of exemplary samples by using epitope excision approach (NS 31250-1334 and IgG Fc 345-355 ). The sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 40 publications
(59 reference statements)
1
38
0
1
Order By: Relevance
“…For Western blot analysis, 25 mg of protein extracts, each comprising equal amounts of proteins from patient's Group A and B, were run on 4% to 20% gradient precast gels (Bio-Rad) and transferred onto Protran Nitrocellulose Transfer membrane (Schleicher-Schuell, Dassel, DE, Germany) using Trans Blot Semi-dry Transfer cell (Bio-Rad) (29). The membranes were blocked with 2% nonfat milk.…”
Section: Immunoblotting Analysismentioning
confidence: 99%
“…For Western blot analysis, 25 mg of protein extracts, each comprising equal amounts of proteins from patient's Group A and B, were run on 4% to 20% gradient precast gels (Bio-Rad) and transferred onto Protran Nitrocellulose Transfer membrane (Schleicher-Schuell, Dassel, DE, Germany) using Trans Blot Semi-dry Transfer cell (Bio-Rad) (29). The membranes were blocked with 2% nonfat milk.…”
Section: Immunoblotting Analysismentioning
confidence: 99%
“…Even though we did not identify specific HCV epitopes for the IgM anti-HCV antibodies, previous studies have shown that autoreactive IgM might originate in response to core or even other HCV Ags, such as the NS3 or E2 proteins, with mimicry of Ig motifs. The binding of IgM with IgG Fc might be due to coincidental crossreactivity (32,33,34). Interestingly, no IgM activity against HCV was detected in the small number of patients tested with type I cryoglobulinemia.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 The recognition of a molecular mimicry between HCV-specific proteins and certain autoantigens and of NS5A and core proteins of HCV being able to stimulate autoantigen production by the immune system may also account for both B-lymphocyte activation and autoimmune reactions in MCS. 30 All these abnormalities could be the consequence of an altered expression of regulatory microRNAs (miRNAs), as recently suggested by the finding of an overexpression of miRNA 17-92 in the circulating lymphocytes of patients with MC that was reverted by interferon therapy. 31 TREATMENT OF MIXED CRYOGLOBULINEMIA SYNDROME Antiviral therapy with interferon is the mainstay for the long-term control of MCS because HCV RNA suppression leads to interruption of lymphocyte stimulation by HCV and results in an improvement or disappearance of most clinical and laboratory manifestations of virus-related MCS ( Table 1).…”
Section: Mixed Cryoglobulinemiamentioning
confidence: 95%